Near infrared light triggered reactive oxygen species responsive nanoparticles for chemo-photodynamic combined therapy. Issue 15 (6th April 2018) - Zhang, Xuefei; Huang, Binyao; Shen, Yifeng; Yang, Chanzhen; Huang, Zeqian; Huang, Yanjuan; Xu, Xiaoyu; Jiang, Yali; Sun, Xiaoqi; Li, Xining; Yan, Mina; Zhao, Chunshun
Abstract : Nanoparticles with ROS-responsive properties could realize spatial and temporal drug release under NIR irradiation and the excess ROS could be used for PDT. Abstract : Currently, the strategy of combining photodynamic therapy (PDT) and chemotherapy for enhancing cancer therapeutic efficiency has aroused extensive interest. Nonetheless, weaknesses such as low local concentration, uncontrollable release of the drug, a non-suitable treatment light source, and a low response to the tumor site of PDT lead to the combined treatment effect not being ideal. Herein, we proposed simple and intelligent ROS-responsive zinc phthalocyanine sensitized TiO2 nanoparticles which conjugated with chlorambucil (CBL) (mTiO2 –BCBL@ZnPC NPs) in an attempt to solve these issues. Not only were the nanoparticles triggered in near infrared radiation (NIR) for PDT with various reactive oxygen species (ROS) being generated, but the nanoparticles also realized the controllable release of CBL by H2 O2, a major kind of ROS, through cleavage of the phenylboronic ester between CBL and the nanoparticle. Impressively, the controllable release of CBL under NIR irradiation showed an on–off characteristic and time dependency. In addition, the well-defined mTiO2 –BCBL@ZnPC NPs with a 30 nm average diameter showed good stability and biocompatibility. The in vitro cytotoxicity studies demonstrated that the mTiO2 –BCBL@ZnPC NPs were more cytotoxic under NIR irradiation than the mTiO2 @ZnPC NPs and CBL, while the mTiO2 –BCBL@ZnPC NPs were less cytotoxic under dark conditions. The above results implied that photo-controlled drug release is a promising choice for cancer therapy due to its high selectivity, good safety and low side-effects, and would be expected to be used in chemo-photodynamic combined therapy for improving the therapeutic efficiency.